Approaches to accelerating the study of new antiretrovirals in pregnancy. (19th July 2022) - Abrams, Elaine J.; Calmy, Alexandra; Fairlie, Lee; Mahaka, Imelda C.; Chimula, Lameck; Flynn, Patricia M.; Kinuthia, John; Myer, Landon; Khoo, Saye H.; Musoke, Philippa; Zwerski, Sheryl; Zech, Jennifer M.; et al.
Abstract: Introduction: Women who are pregnant or who could become pregnant experience delayed access to or underinformed use of important new antiretroviral (ARV) drugs because of traditional drug development processes that ostensibly aim to reduce potential harm but effectively fail to ensure that timely information about safe and effective use in pregnancy is available. Discussion: The World Health Organization and International Maternal, Pediatric, Adolescent Antiretroviral Clinical Trials Network convened a year‐long workshop on "Approaches to Enhance and Accelerate Study of New Drugs for HIV and Associated Infections in Pregnant Women." Workshop participants were tasked with defining key principles and optimal approaches to including pregnant women in pre‐ and post‐licensure trials in order to accelerate the availability of pharmacokinetic and safety data for new ARV agents in pregnancy. ARV efficacy in pregnancy and ARV efficacy for prevention of vertical transmission can be extrapolated from proof of efficacy in non‐pregnant adults, provided that drug levels in pregnancy are similar. However, short‐term safety and pharmacokinetics must be studied directly in pregnant women and should be conducted and included in initial licensure for all new ARVs. Accelerating the timeline for completion of pre‐clinical studies is essential for pregnancy short‐term safety and pharmacokinetic studies to be safely completed by the time a drug is licensed. Composite key pregnancy, birth and neonatal outcomes are critical for drugs expected to have broad use, and studies should be initiated at or soon after drug licensure. Teratogenicity risk cannot be feasibly assessed before drug licensure and will depend on robust post‐marketing surveillance systems. With some modifications, these principles will apply to ARVs used for prevention, two‐drug regimens, long‐acting ARVs and ARVs administered through novel delivery systems. Conclusions: Implementation of the proposed principles and framework will enhance and accelerate the study of new ARVs in pregnancy, resulting in more timely, equitable and informed access to new ARVs for pregnant women.